Preliminary Survey in preparation for the implementation of ERAS at Dr Soetomo Hospital - Veterini, Anna; Firdaus, Khildan Miftahul; Semedi, Bambang Pujo; Putri, Herdiani Sulistyo; Fitritati, Mariza; Mutiar, Airi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Background Medical science has developed rapidly. One of them is ERAS (Enhanced Recovery After Surgery) which is a multidisciplinary team development pathway for perioperative methods that offer a variety of benefits. Some of the advantages of the ERAS method are speeding up the post-operative recovery period, economic benefits, and shortening the Length of Stay (LOS) by minimizing surgical stress so that the patient quickly returns to a normal physiological state. Objective This study aims to analyze the readiness of the team that will support the ERAS application at General Academic Hospital (RSUD) Dr Soetomo. Methods This is an observational analytic study with a cross-sectional design using a questionnaire. Patient baseline data were taken from the examination at the anesthesiology outpatient clinic. Assessment for patient understanding was carried out directly after a brief explanation of ERAS method by the researcher. The patient's level of understanding was assessed by two investigators and rated on a scale of 1 to 5. Primary data and assessment of understanding of doctors and medical personnel were filled in independently by research subjects on online forms and rated on a scale of 1 to 5. Data was collected from March 23 to April 14 2022, at RSUD Dr. Soetomo Surabaya. The analysis results are considered significant if the p-value is less than 0.05. The analysis was carried out using SPSS 19 software. Results Most patients planned to undergo surgery in the field of urology (82.9%), followed by caesarean section (14.6), and almost all patients or their families agreed to surgery using the ERAS method (95.1%). The medical team consists of 110 doctors from 4 areas of expertise, namely specialist doctors and residents in anesthesiology, urology surgery, obstetrics and gynecology, as well as orthopedics and traumatology. The health team consists of 56 personnel, namely anesthesiologists, surgeons, recovery room nurses, nutritionists and pharmacists. The majority (61%) of health workers had heard about ERAS and stated that ERAS was ready to be implemented at RSUD Dr. Soetomo (89%). Most doctors stated that ERAS was ready to be implemented at Dr. Soetomo and its human resources and facilities are considered qualified. Conclusion The ERAS method at RSUD Dr. Soetomo is considered quite ready to start, especially the Obsgyn study program, which is supposed to have an excellent level of understanding of ERAS and is enthusiastic to begin immediately. The patient group can be said to understand and accept the ERAS method well as a perioperative method for handling their cases.